Prolonged cycling lowers subsequent running mechanical efficiency in collegiate triathletes - J. A. Stewart; E. K. Merritt; D. E. Lidstone; J. M. McBride; K. A. Zwetsloot (BMC, 2022)
Abstract Background A significant challenge that non-elite collegiate triathletes encounter during competition is the decline in running performance immediately after cycling. Therefore, the purpose of this study was to determine if performing a 40-km bout of cycling immediately before running would negatively influence running economy and mechanical efficiency of running during simulated race conditions in collegiate triathletes. Methods Eight competitive club-level collegiate triathletes randomly performed two trials: cycling for 40 km (Cycle-Run) or running for 5 km (Run-Run), immediately followed by a four-minute running economy and mechanical efficiency of running test at race pace on an instrumented treadmill. Blood lactate, respiratory exchange ratio, mechanical work, energy expenditure, and muscle glycogen were also measured during the four-minute running test. Results Mechanical efficiency of running, but not running economy, was significantly lower in Cycle-Run, compared to Run-Run (42.1 ± 2.5% vs. 48.1 ± 2.5%, respectively; p = 0.027). Anaerobic energy expenditure was significantly higher in the Cycle-Run trial, compared to the Run-Run trial (16.3 ± 2.4 vs. 7.6 ± 1.1 kJ; p = 0.004); while net (151.0 ± 12.3 vs. 136.6 ± 9.6 kJ; p = 0.204) and aerobic energy expenditure (134.7 ± 12.3 vs. 129.1 ± 10.5 kJ; p = 0.549) were not statistically different between trials. Analysis of blood lactate, respiratory exchange ratio, mechanical work, and changes in muscle glycogen revealed no statistically significant differences between trials. Conclusions These results suggest that mechanical efficiency of running, but not running economy, is decreased and anaerobic energy expenditure is increased when a 40-km bout of cycling is performed immediately before running in collegiate triathletes.